2014
DOI: 10.1111/opo.12170
|View full text |Cite
|
Sign up to set email alerts
|

Provocative intraocular pressure challenge preferentially decreases venous oxygen saturation despite no reduction in blood flow

Abstract: Mild, acute IOP elevation increases arterio-venous oxygen saturation differences primarily through lowering venous oxygen saturation, suggesting increased oxygen consumption by healthy neurons when physiologically stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
(57 reference statements)
2
6
0
Order By: Relevance
“…The reduction in arterial oxygen saturation is an unexpected finding but could be due to the aforementioned diffusional oxygen exchange mechanism in consequence of the largely reduced venous oxygen saturation possibly enhanced by a decrease in blood flow. A similar pattern of oxygen saturation changes like in our study has been shown in healthy subjects during a moderate experimental increase of intraocular pressure for a maximum of 5 min insofar as oxygen saturation significantly decreased in retinal veins and tended to be reduced in retinal arteries (O'Connell et al 2015). After IVI, there is an immediate increase in intraocular pressure, which usually normalizes not earlier than after 20 min and sometimes stays highly elevated for more than 1 hr (Bracha et al 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The reduction in arterial oxygen saturation is an unexpected finding but could be due to the aforementioned diffusional oxygen exchange mechanism in consequence of the largely reduced venous oxygen saturation possibly enhanced by a decrease in blood flow. A similar pattern of oxygen saturation changes like in our study has been shown in healthy subjects during a moderate experimental increase of intraocular pressure for a maximum of 5 min insofar as oxygen saturation significantly decreased in retinal veins and tended to be reduced in retinal arteries (O'Connell et al 2015). After IVI, there is an immediate increase in intraocular pressure, which usually normalizes not earlier than after 20 min and sometimes stays highly elevated for more than 1 hr (Bracha et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…However, the study of O'Connell et al we mentioned above not only reported an increase in AV difference during the phase of moderately raised intraocular pressure but also showed that retinal blood flow was not diminished, whereas pattern electroretinogram was significantly disturbed. This indicates that already during moderate elevation of intraocular pressure in healthy eyes there is an increased oxygen consumption of stressed retinal ganglion cells and neurons suggesting an increased metabolic demand alongside unaltered retinal perfusion (O'Connell et al 2015). During an acute decrease of ocular perfusion pressure, oxygen extraction has been proposed to play an important role to maintain retinal function and the oxygen extraction rate per unit blood flow can increase to compensate for mild ischaemia and to maintain cellular metabolism (He et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…; O'Connell et al. ). Moreover, clinical and population‐based studies reported that changes in retinal oxygen saturation and vessel diameter are associated with pathological degeneration of retina in eyes with ocular diseases, such as diabetes, primary open‐angle glaucoma and retinitis pigmentosa (Ramm et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is a key measure as the high rate oxygen consumption in retina is critical for ocular function. Various factors can affect the oxygen saturation of retinal vessels: changes in the oxygen concentration of the environment; metabolic disease; and changes in ocular structure (Nagel et al 2004;Tayyari et al 2009;Lange & Bainbridge 2012;Palkovits et al 2014;O'Connell et al 2015). Moreover, clinical and population-based studies reported that changes in retinal oxygen saturation and vessel diameter are associated with pathological degeneration of retina in eyes with ocular diseases, such as diabetes, primary open-angle glaucoma and retinitis pigmentosa (Ramm et al 2014;Turksever et al 2014;Cheung et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Huynh and Feld adjustment is similar but is regarded as more liberal than Greenhouse and Geisser. When search terms were used to specifically identify those articles which tested and corrected for sphericity, 14/66 (21%) used Mauchly's test, 24 47/66 (71%) the Greenhouse-Geisser correction, [25][26][27] and 5/66 (8%) the Huynh and Feld correction, 28 62% of which were published in the period 2012 to the present. A problem with these procedures, however, is that they may not protect against multiple testing using post-hoc tests after RM-ANOVA especially if an overall error term is used.…”
Section: Resultsmentioning
confidence: 99%